THE INFLUENCE OF LEADERSHIP, WORK CLIMATE AND SPIRIT ON DISCIPLINE ELEMENTARY SCHOOL TEACHERS IN BATU AMPAR DISTRICT TANAH LAUT REGENCY - Sundari, Sundari; Aslamiah, Aslamiah; Ngadimun, Ngadimun (Journal of K6, Education and Management, 2019)
Discipline is the attitude of willingness and willingness of a person to comply with and obey the rules and regulations that apply around him. Discipline is also influenced by several factors namely the leadership of the principal, the work climate and work spirit . The purpose of this study was to analyze the direct and indirect effects of leadership, work climate and work spirit on the discipline of elementary school teachers in Batu Ampar District, Tanah Laut Regency. This research is quantitative with cross sectional method and using the technique of correlation (correlation research). The study population was 165 teachers and 117 respondents were taken as the study sample by proportional e random sampling technique . Data collection uses instrument questionnaires and data analysis using test instruments (validity and reliability testing), descriptive analysis, classic assumption test, linear regression analysis and path analysis. The results of this study show that 1) there is a positive and significant influence on the principal's leadership directly on the disciplinary variables of SDN teachers in Batu Ampar District, Tanah Laut Regency. 2) threre is a significant and positive influence school leadership directly on spirit Elementary School teacher in the district of Batu Ampar District, Tanah Laut Regency. 3) threre is a positive and significant influence climate school work directly against the SDN teacher discipline in Batu Ampar District, Tanah Laut Regency. 4) threre is a positive and significant influence climate school work directly against the SDN teacher spirit in Batu Ampar District, Tanah Laut Regency. 5) threre is positive and significant influence teachers' spirit directly to the discipline teacher of SDN in Batu Ampar District, Tanah Laut Regency. 6) threre is a significant and positive influence school leadership indirectly through the spirit of teachers to discipline Elementary School teacher in Batu Ampar District, Tanah Laut Regency. 7) threre is positive and significant influence school work climate indirectly through the spirit of teachers to discipline Elementary School teacher in Batu Ampar District, Tanah Laut Regency. Suggestions to school principals and teachers can maintain the organizational climate by establishing good relations among employees such as the mutual trust and mutual support between employees can create good work discipline .